Non-coding RNAs as potential biomarkers in osteosarcoma - Fan, Lijuan; Zhong, Zhenhao; Lin, Yubo; Li, Jitian (Frontiers in Genetics, 2022)
Osteosarcoma (OS) is a primary solid malignant tumor that occurs most frequently in the metaphysis of long bones. More likely to happen to children and adolescents. OS has high mortality and disability rate. However, the etiology and pathogenesis of OS have not been fully understood till now. Due to the lack of effective biomarkers, OS cannot be precisely detected in the early stage. Application of next-generation and high-throughput sequencing have identified thousands of abnormal expression non-coding RNAs (ncRNAs) in OS. Growing evidences have suggested the ncRNAs, such as microRNAs (miRNAs), long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), have played an important role in the tumorigenesis and progression of OS. Thus, they can be served as novel biomarkers for diagnosis, treatment and prognosis. This review summarized the application of ncRNA as biomarkers in OS in detail, and discussed the limitation and future improvement of the potential biomarkers.